Preparation of Graphene/TiO2 Composite Nanomaterials and Its Photocatalytic Performance for the Degradation of 2, 4-Dichlorophenoxyacetic Acid. (25th August 2016) - Huang, Donggen; Yang, Tianzi; Mo, Zhuanghong; Guo, Qin; Quan, Shuiqing; Luo, Cui; Liu, Lei
Abstract : The graphene (GR) was prepared by an improved electrochemical stripping method using a high-purity graphite rod as raw material and high temperature heat reduction in hydrogen atmosphere, and the graphene/TiO2 (GR/TiO2 ) composite nanomaterials were manufactured by the method of sol-gel and high temperature crystallization in hydrogen atmosphere using butyl titanate and electrolysis graphene as precursors. The physical and chemical properties of the composites had been characterized by using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), UV-Vis spectrophotometer (UV-Vis), scanning electron microscopy (SEM), Transmission Electron Microscope (TEM), and specific surface area (SSA) by BET method. The photocatalytic properties of GR/TiO2 composites nanomaterials in anoxic water were studied by using 2, 4-dichlorophenoxyacetic acid (2, 4-D) as probe. The results showed that graphite was well intercalated and peeled by a facile electrolysis method in different electric field environment; a well dispersed and rings structure of graphene was prepared by coupling ultrasound-assisted changing voltage electrochemical stripping technology. The as-prepared GR/TiO2 composites had good performance for the photocatalytic degradation of 2, 4-D in anoxic water; the chlorines were removed from benzene ring; the middle products of dichlorophenol, chlorophenol, phloroglucinol, and so forth were produced from the photocatalytic redox reaction of 2, 4-D in anoxic water; parts of 2, 4-D were decomposed completely, and CO2 and H2 O were produced.